The Big Dig: Geological and other outcomes of the 2008–2009 Freshwater Brook sewer replacement project, Halifax, Nova Scotia, Canada - Jamieson, Rebecca A. (Atlantic Geoscience, 2025)
In 2008 Halifax Regional Municipality undertook a major construction project to replace the underground sewer system that carries Freshwater Brook from the Halifax Commons to its outlet at the southeastern end of the Halifax Peninsula. The project was necessary because the existing system did not meet modern standards and the old pipes ran under city blocks and were therefore inaccessible in many places for maintenance and repair. The first part of the project (2008-09) involved installing a modern dual pipe system along a route that crossed the predicted locations of the boundary between the Cunard and Bluestone Quarry formations of the Halifax Group, and the biotite-in and andalusite-in isograds of the contact aureole of the South Mountain Batholith. Bedrock was exposed along much of the excavated trench, which was nearly 10 m deep in many places. Outcrop observations and samples from the trench revealed that the Cunard-Bluestone Quarry contact runs under the Sobeys parking lot, between Fenwick and Queen streets. The andalusite-in isograd in the Cunard Formation can be traced as far as the west end of Fenwick Street. The cordierite-in isograd lies east of the study area, and the biotite-in isograd to the west. The lithology and isograd map for south end Halifax has been updated based on these results. Problems including uncertain subsurface location of the old pipes, contaminated soil, and carbon monoxide migration into residential buildings contributed to significant delays and cost overruns; some of these might have been mitigated with better knowledge of the subsurface geology.